Dynamics of rising CO2 bubble plumes in the QICS field experiment: Part 2 – Modelling. (July 2015) - Dewar, Marius; Sellami, Nazmi; Chen, Baixin
Highlights: The dynamics of leaked bubble plumes are analysed from the QICS experiment. Bubble distribution and interaction sub-models validated against experimental data. Interactions bring simulation results closer to that experienced in the experiment. Improved small scale two phase model applied to simulate the full QICS experiment. Limitations from neglecting both topography and the CO2 solution leaked from seabed. Abstract: An oceanic two-phase plume model is developed to include bubble size distribution and bubble interactions, applied to the prediction of CO2 bubble plume and CO2 solution dynamics observed from the recent QICS field experiment in the Scottish sea at Ardmucknish Bay. Observations show bubbles form at between 2 and 12 mm in diameter, where the inclusion of the interactions within the simulations brings results of bubble plumes closer to that of the experiment. Under a given leakage flux, simulations show that the bubble size affects the maximum p CO2 dissolved in the water column, while the bubble interactions affect the vertical bubble distribution. The maximum modelled p CO2 increases from a background 360 μatm to 400, 427 and 443 μatm as CO2 injection rates increase from 80, 170 to 208 kg/day respectively at low tide. An increase of the leakage rate to 100% of the injection rate shows the maximum p CO2 could be 713 μatm, approaching the mean p CO2 observed of 740 μatm during the high leakage component of the experiment, suggesting that the flux may be greater than estimated due to the varied flux and activity across the pockmarks during the leakages.